Service Quality, Price, and Customer Loyalty: Moderating Role of Customer Satisfaction - Barida Rakhma Nuranti; Sri Rahayu; Ayu Diana Ansori; Puteri Awaliatush Shofro; Muhammad Ardana Tibaroiya; Adhi Nugroho (Journal of Research in Social Science and Humanities, 2024)
The purpose of this study is to test and analyze the influence of service quality and price on customer satisfaction, test and analyze the influence of service quality, price, and customer satisfaction on customer loyalty. In addition, this study aims to examine the indirect influence between price and service quality on customer loyalty through customer satisfaction. A quantitative approach was used in this study, with the population and sample being consumers of Pamella Supermarket in D.I. Yogyakarta. The sampling technique uses purposive sampling, with the criteria of at least 17 years old, male and female gender, having shopped at Pamella Supermarket at least 2 times. The data was collected through the distribution of online questionnaires to respondents, and the data was processed with SEM PLS version 3. The results of the study found that service quality and price have an effect on customer satisfaction. Service quality and customer satisfaction have a positive and significant effect on customer loyalty. However, price does not have a significant effect on customer loyalty. In addition, this study proves that price and service quality have a direct and indirect effect on customer loyalty, namely through customer satisfaction. In other words, the consumer satisfaction variable can act as a mediating variable in the influence of price and service quality on Pamella Supermarket customer loyalty. This research provides theoretical and practical recommendations to build customer loyalty in retail businesses and other businesses.